Peran Digitalisasi dan Branding UMKM dalam Meningkatkan Daya Saing Ekonomi Lokal Berdasarkan SDG 8 dan SDG 9 : Studi Kasus Apotek Kasih Ibu dan Herawati Cake di Balige - Faris Andrawika Harahap; Ahmad Yusuf Akbar; Zuhrinal M Nawawi; Tuti Anggraini (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to implement and evaluate the role of digitalization and branding strategies in increasing competitiveness and developing the local economy of two Micro, Small, and Medium Enterprises (MSMEs) in Saribu Raja Janji Maria Village, Balige, namely Apotik Kasih Ibu and Herawati Cake. This activity uses a qualitative descriptive method involving three stages: 1) initial observation and assessment; 2) intervention (implementation of QRIS at Apotik Kasih Ibu and development of brand identity strengthening strategies at Herawati Cake); and 3) final evaluation through interviews and documentation. The results of the activity show a measurable impact of the intervention, where the implementation of QRIS at Apotik Kasih Ibu increases the efficiency of cashier transaction times by an average of 30%, and increases customer convenience. The branding strategy at Herawati Cake has succeeded in strengthening the business image as shown by a 45% increase in social media engagement and expansion of market reach outside the sub-district. These two interventions support SDG 8 and SDG 9. The synergy between digitalization and branding has proven effective as a model for accelerating modern and sustainable village economic development, and has the potential to be replicated as a best practice for strengthening the community-based digital economy.